Clinical and Demographic Characteristics of Intraocular Foreign Body Injury in a Referral Center: 3 Years Experience - Ibraheem Anifat Boladale, Ibraheem Waheed Ademola, Nazmum Naha (Pakistan Journal of Ophthalmology, 2016)
Purpose: To describe clinical and demographic features of patients with intraocular foreign body (IOFB) injuries in a referral center with a view to provide useful information on the disease in our country. Study Design: Retrospective case review Place and Duration of Study: From January, 2013 to December, 2015 at Department of Vitreo-retinal Surgery, Ispahani Islamia Eye Institute and Hospital, Dhaka, Bangladesh Materials and Methods: We retrospectively reviewed 64 case files of patients who were treated for IOFB injuries between January, 2013 and December, 2015. Data on age, sex, ocular laterality, nature of foreign body, entry point/ visual acuity, injury to surgery time, presence of endophthalmitis and siderosis bulbi were extracted and evaluated. Results: Case files of 64 patients consisting 64 eyes were analyzed. The age of the patients ranged between 2-55 years. Males were mostly affected accounting for 95.3% of all cases. Left eye was slightly more affected (33, 51.6% versus 31, 48.4. The commonest entry site was cornea accounting for (60.9%). Majority (81.1%) of the cases had entry visual acuities which were equal or worse than 6/60 in of the cases. Removed intraocular foreign bodies were identified to be metallic (Iron) in 63 (98.4%) cases. Conclusion: There is need for increase awareness about wearing safety glasses at work to reduce the burden of this avoidable blindness. Key Words: Intraocular, Foreign body, Endophthalmitis, Evisceration.